Evaluation of Antibacterial Potential of Ethanol Extract from Kirinyuh (Chromolaena odorata L.) Leaves Against Salmonella typhi - Nita Hastuti; Emerensiana Surasma Surung (Biofaal Journal, 2025)
Kirinyuh leaves (Chromolaena odorata L.) are known to possess antibacterial activity against Salmonella typhi, the causative agent of typhoid fever. The leaves contain secondary metabolites such as flavonoids, saponins, tannins, and steroids, which contribute to their inhibitory effect on bacterial growth. This study evaluated the antibacterial efficacy of ethanol extract of C. odorata leaves at concentrations of 50%, 75%, and 100% using the Total Plate Count (TPC) method. Five treatment groups were tested: ciprofloxacin (positive control), distilled water (negative control), and kirinyuh extract at three concentrations. The results revealed five distinct statistical subsets, with significant differences observed between treatments in different subsets. Mean bacterial counts increased progressively from 24.7 in the positive control to 138.3 in the negative control. These findings demonstrate that ethanol extract of kirinyuh leaves effectively inhibits S. typhi growth, with the degree of inhibition varying according to extract concentration.